Factors affecting secondary post-tonsillectomy hemorrhage: a case—control study - Hesham Negm; Ahmed Atef; Hesham Lasheen; Ahmed A. Kamel; Khaled Azooz; Osama Elhoussainy (The Egyptian Journal of Otolaryngology, 2017)
Abstract Background Tonsillectomy is one of the commonest otolaryngological procedures performed. Multiple reports have demonstrated the safety of ambulatory (outpatient) pediatric Tonsillectomy, however Post-tonsillectomy hemorrhage remains the most serious complication of tonsillectomy. Patients and methods In this work, we analyzed different parameters including patient’s age, gender, type of surgery “Tonsillectomy or Adenotonsillectomy”, technique “Cold dissection or Bipolar”, evidence of tonsillar bed infection and pre-operative hemoglobin level in two groups of patients indicated for tonsillectomy. One group of 80 patients didn’t suffer from posttonsillectomy bleeding as a control group; the other of 20 patients having secondary post-tonsillectomy bleeding. Results According to our statistical analysis and data, no significant difference between the two groups regarding the occurrence of secondary post-tonsillectomy in the following parameters: patient’s age, gender, type of surgery “Tonsillectomy or Adenotonsillectomy” and preoperative hemoglobin level. Conclusion However there was higher incidence of secondary post tonsillectomy bleeding in patients operated by bipolar scissors. Also evidence of tonsillar bed infection raises the possibility of secondary post-tonsillectomy bleeding occurrenc.